Development and Validation Method for Simultaneous Investigation of Ambroxol Hydrochloride and N-Acetyl Cysteine In Bulk And Pharmaceutical Formulation By RP-HPLC. - Thote, Lokesh; Dhabarde, Disha; Baheti, Jagdish; Borkar, Shilpa; Bhusari, Swati (Asian Journal of Pharmaceutical Research and Development, 2022)
A simple, precise and rapid reverse phase HPLC- SPD 20-Amethod has been developed and validated for the simultaneous investigation of Ambroxol Hydrochloride (AMB) and N-Acetyl Cysteine (NAC) in tablet dosage form. The mixture of (AMB) and (NAC) was separated on C18 5µm.column (4.5 µm × 25 cm). All separation were monitored with a SPD-20A UV-Vis detector on 210 – 400 nm wavelength at ambient temperature and flow rate of 1 ml/min. The mobile phase was phosphate buffer: acetonitrile (75:25) and pH 2.5 adjusted with dilute ortho-phosphoric acid. The retention time of AMB and NAC were found to be 8.4024 and 3.35088 respectivelythe resolution was 9.86346. The method was mean recoveries in the range of 100.4 to 100.15 for all components. The developed method can be use for the routine analysis of AMB and NAC in tablet dosage form.